2019
DOI: 10.1101/556035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dopamine receptor D5gene shows signs of independent erosion in Toothed and Baleen whales

Abstract: To compare gene loci considering a phylogenetic framework is a promising approach 11 to uncover the genetic basis of human diseases. Imbalance of dopaminergic systems is suspected 12 to underlie some emerging neurological disorders. The physiological functions of dopamine are 13 transduced via G-protein-coupled receptors, including DRD5 which displays a relatively higher 14 affinity towards dopamine. Importantly, DRD5 knockout mice are hypertense, a condition 15 emerging from an increase in sympathetic tone. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Indeed, exposure to either psychosocial stress or acute administration of the inverse agonist acted in the opposite direction than the cannabinoid agonist did 85,92 . Dopaminergic neurotransmission is essential for cerebral function, controlling various physiological mechanisms including cognition, locomotion, neuroendocrine activity, emotional and motivational aspects 93 . Recent studies have demonstrated that midbrain dopaminergic neurons are particularly vulnerable to microtubule disruptions 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, exposure to either psychosocial stress or acute administration of the inverse agonist acted in the opposite direction than the cannabinoid agonist did 85,92 . Dopaminergic neurotransmission is essential for cerebral function, controlling various physiological mechanisms including cognition, locomotion, neuroendocrine activity, emotional and motivational aspects 93 . Recent studies have demonstrated that midbrain dopaminergic neurons are particularly vulnerable to microtubule disruptions 94 .…”
Section: Discussionmentioning
confidence: 99%